Investigation into the mechanisms by which microwave heating enhances separation of water-in-oil emulsions - Binner, Eleanor; Robinson, John P.; Silvester, S.A.; Kingman, S.W.; Lester, Edward (Elsevier, 2014)
The separation of water-in-oil emulsions made with Azeri crude was investigated using natural gravity settling and microwave heating techniques. Separation times could be reduced by an order of magnitude compared with untreated emulsions. Increasing the salinity of the water phase leads to a 15% average decrease in the settling time for untreated emulsions compared with over 90% for microwave-heated emulsions. An image analysis technique showed that the observed increases in settling time could not be attributed to changes in viscosity alone. Significant coalescence of water droplets occurs during microwave heating, however the effects of coalescence and viscosity reduction cannot be completely decoupled. Despite this, it is clear that it is the thermal effect of microwave heating that leads to improvements in settling times, and that any advantages in microwave heating over conventional heating can be explained by selective heating of the aqueous phase rather than so-called non-thermal effects.